Actors as Co-Creators in Contemporary Latvian Theatre: Aesthetical and Social Aspects - Rodiņa, Ieva (Nordic Theatre Studies, 2023)
In Latvian theatre, the last decade has been a time of significant changes regarding the working methods of independent theatre movements. Two of the oldest independent theatres in Riga – Dirty Deal Teatro and Ģertrūde Street Theatre – have become a centre for various theatre productions, therefore moving towards the model of state repertoire theatres. Meanwhile, in recent years, several new theatre companies and creative groups have appeared in the field. Theatre troupe KVADRIFRONS, formed by four young actors having just graduated from the Latvian Academy of Culture, as well as the theatre company esARTe, led by director and teacher Elmārs Seņkovs and the ‘scandalous’ young actors trained in the so-called puppet theatre course at the Latvian Academy of Culture, – these are just a few examples of the new creative formations in Latvian theatre. While in repertoire theatre the creative process mostly lies on the shoulders of the stage director, the aforementioned theatre companies highlight the importance of the actor as co-creator – both in the artistic (devised theatre methods), and the administrative process (actors as managers, etc.). Has the profession of actor changed from performer to administrator? How does the administrative status of the newly founded theatre companies influence the work of freelance actors? How has the status of the actor changed in today’s society? The research tackles the topic of actor as co-creators focusing on the examples and experiences of new independent Latvian theatre companies and including significant social, as well as aesthetical aspects.